2023
DOI: 10.32479/ijeep.14185
|View full text |Cite
|
Sign up to set email alerts
|

Do Clean Energy and Financial Innovation Induce SME Performance? Clarifying the Nexus between Financial Innovation, Technological Innovation, Clean Energy, Environmental Degradation, and SMEs Performance in Bangladesh

Abstract: The economic contribution of small and medium enterprises (SMEs) has been well appreciated and documented in the literature. On the other hand, another domain of studies has concentrated on discovering the key determinants of SMEs' growth and survival. The motivation of the study is to gauge the nexus between financial innovation, technological innovation, clean energy, environmental degradation, and SME performance in Bangladesh for the period 1991-2019. The study has implemented Autoregressive Distributed La… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…It can be inferred that countries with higher levels of institutional quality create a conducive environment for technological advancements and effective policy suggestions. Our study is supported by the exiting literature such as [7,35,38,91]. Institutional quality encompasses the robustness and effectiveness of a nation's institutions, encompassing its legal framework, regulatory environment, governance structures, and policies.…”
Section: Resultsmentioning
confidence: 59%
See 2 more Smart Citations
“…It can be inferred that countries with higher levels of institutional quality create a conducive environment for technological advancements and effective policy suggestions. Our study is supported by the exiting literature such as [7,35,38,91]. Institutional quality encompasses the robustness and effectiveness of a nation's institutions, encompassing its legal framework, regulatory environment, governance structures, and policies.…”
Section: Resultsmentioning
confidence: 59%
“…The literature review on the nexus between trade openness and technological innovation suggests a positive relationship between trade openness and technological innovation [4,6,[34][35][36][37][38][39][40][41][42]. Gong [43], Zhang, et al [44] found that economic openness promotes economic growth and innovation.…”
Section: Trade Openness Led To Technological Innovationmentioning
confidence: 99%
See 1 more Smart Citation
“…The nonlinear framework introduced by Shin et al [36] has gained popularity in empirical evaluation for investigating asymmetric effects. This approach has been adopted by several researchers, as evidenced by publications such as [37][38][39][40]. This study evaluates the asymmetric effects of EQ and IQ on TO by decomposing their shocks into positive and negative components, in accordance with recent research.…”
Section: Introductionmentioning
confidence: 95%
“…Trade policy measures imposed by the current administration, including tariffs on imported solar panels and components, have led to increased costs for developers and delayed or canceled projects. The additional tariffs on imported steel and aluminum could also raise costs for the renewables industry (Qamruzzaman and Kler, 2023;Lin and Qamruzzaman, 2023). The continued uncertainty around trade policy will likely harm the demand for renewable energy in the United States.…”
mentioning
confidence: 99%